Sustained release of brimonidine from BRI@SR@TPU implant for treatment of glaucoma - Yujin Zhao; Chang Huang; Zhutian Zhang; Jiaxu Hong; Jianjiang Xu; Xinghuai Sun; Jianguo Sun (Taylor & Francis Group, 2022)
Glaucoma is the leading cause of irreversible vision loss worldwide, and reduction of intraocular pressure (IOP) is the only factor that can be interfered to delay disease progression. As the first line and preferred method to treat glaucoma, eye drops have many shortcomings, such as low bioavailability, poor patient compliance, and unsustainable therapeutic effect. In this study, a highly efficient brimonidine (BRI) silicone rubber implant (BRI@SR@TPU implant) has been designed, prepared, characterized, and administrated for sustained relief of IOP to treat glaucoma. The in vitro BRI release from BRI@SR@TPU implants shows a sustainable release profile for up to 35 d, with decreased burst release and increased immediate drug concentration. The carrier materials are not cytotoxic to human corneal epithelial cells and conjunctival epithelial cells, and show good biocompatibility, which can be safely administrated into rabbit's conjunctival sac. The BRI@SR@TPU implant sustainably released BRI and effectively reduced IOP for 18 d (72 times) compared to the commercial BRI eye drops (6 h). The BRI@SR@TPU implant is thus a promising noninvasive platform product for long-term IOP-reducing in patients with glaucoma and ocular hypertension.